Estudo dos remanescentes de supernova N49 e N63a - Melnik, Igor Antonio Cancela (2013)
In this work, we present the results of an observational study regarding the supernova remnants N49 and N63A. The longslit spectrophotometric data of N49 were obtained with the Cassegrain spectrograph attached to the 1,6 m telescope of the Laborat´orio Nacional de Astrof´ısica. The data covered the range between 6000 to 7000 °A, being possible to detect the lines [S ii] λλ 6716, 6731, which ratio was used to determine the electron density. One dimensional spectra with an aperture size of 2.3 ′′ were extracted from this date and were used to built flux, velocity dispersion and radial velocity maps. The electron density map showed signs of interaction between the southeast region of N49 and a molecular cloud. This map also shows the existence of a gradient that confirmed previous studies, revealing that the electron density varies by a factor of 3 between the east and west borders. The densest areas (Ne > 2000 cm−3) were observed at the east border, near the brightest areas in optics. However the dense areas at the northeast border have low brightness. From the total Hα flux, an ionized mass of ≈ 207±66 M⊙ was inferred. A rms density of ≈ 60 cm−3 was calculated by the Hα surface brightness. We also inferred the filling factor being ≈ 0.002. The radial velocity map associated to the blueshifted component showed a radial symmetry. Points farther from the center had smaller radial velocity than the central ones. The velocity dispersion map also presents a similar radial symmetry, and was interpreted as a projection effect. By constructing an one-dimensional model, we will show that the radial velocity measurements may be caused by the interaction of the blast wave with the interstellar medium with a power-law density profile. The fitting parameters were consistent with previous studies. The longslit data of N63A were colected with the SOAR telescope and covered the range between 3550 to 7500 °A . The [S ii]/Hα and [O i]/Hα ratio maps confirm the conclusion of previous studies and show that the southeastern lobe is photoionized. The [O iii] (λ4959+λ5007)/λ4363 ratio was used to determine a mean electron temperature of 5.0 × 104 K. From the reddening-corrected Hβ flux we estimated a mass of 12 and 35 M⊙ for the photoionized and shock-heated regions, respectively. The Hα/Hβ and the [N ii]/Hα ratio maps show an arc-shaped structure with higher values at the southeast boundary. We also obtained data from N63A with the OPD telescope at 7 distinct positions, from which we constructed a radial velocity map. This map presents a gradient that can be interpreted as a projection by assuming that the observed shock-heated region is a semi-sphere of gas in expansion. The electron density profile observed along the photoionized lobe suggests an interaction between the expanding gas from the supernova remnant with an independent Hii region.